Deaths following vaccination: What does the evidence show? - Miller, Elaine R. (Vaccine, 2015)
Vaccines are rigorously tested and monitored and are among the safest medical products we use. Millions of vaccinations are given to children and adults in the United States each year. Serious adverse reactions are rare. However, because of the high volume of use, coincidental adverse events including deaths, that are temporally associated with vaccination, do occur. When death occurs shortly following vaccination, loved ones and others might naturally question whether it was related to vaccination. A large body of evidence supports the safety of vaccines, and multiple studies and scientific reviews have found no association between vaccination and deaths except in rare cases. During the US multi-state measles outbreak of 2014–2015, unsubstantiated claims of deaths caused by measles, mumps, and rubella (MMR) vaccine began circulating on the Internet, prompting responses by public health officials to address common misinterpretations and misuses of vaccine safety surveillance data, particularly around spontaneous reports submitted to the US Vaccine Adverse Event Reporting System (VAERS). We summarize epidemiologic data on deaths following vaccination, including examples where reasonable scientific evidence exists to support that vaccination caused or contributed to deaths. Rare cases where a known or plausible theoretical risk of death following vaccination exists include anaphylaxis, vaccine-strain systemic infection after administration of live vaccines to severely immunocompromised persons, intussusception after rotavirus vaccine, Guillain-Barré syndrome after inactivated influenza vaccine, fall-related injuries associated with syncope after vaccination, yellow fever vaccine-associated viscerotropic disease or associated neurologic disease, serious complications from smallpox vaccine including eczema vaccinatum, progressive vaccinia, postvaccinal encephalitis, myocarditis, and dilated cardiomyopathy, and vaccine-associated paralytic poliomyelitis from oral poliovirus vaccine. However, making general assumptions and drawing conclusions about vaccinations causing deaths based on spontaneous reports to VAERS – some of which might be anecdotal or second-hand – or case reports in the media, is not a scientifically valid practice.